(untitled) (Transport systems and technologies, 2018)
The article considers the reliability of the bunkering process of ships, as a property of a technical object to save all parameters, which characterize the ability to perform the required functions in the given modes and conditions of use, maintenance, storage and transportation. The description of properties of reliability of technical objects is given: non-failure operation, durability, repairability, safety and readiness. It was suggested to add properties of resource productivity to the reliability properties, which would allow to achieve the goal of checking the effectiveness of the technical object and will show the effectiveness of measures to improve the structure, strategies for maintenance and repair. In order to analyze the reliability of bunkering processes on water transport, the main factors of ensuring the reliability of bunkering (TCSE-analysis) were determined. The grouping of factors is carried out in terms of technical, technological, safety and environmental parameters, which will allow to formalize the reliability function. Carrying out TCSE-analysis of the described conditions allowed to determine their importance and mutual influence in the processes of ensuring the reliability of bunkering. The scheme of the sequence of conducting TCSE-analysis of bunkering reliability has been developed. The characteristics of resource maintenance of bunkering reliability are considered. The characteristics of resource maintenance of bunkering reliability are considered. Given the importance of the group of factors in the system, the coefficient of overall reliability of the bunkering process is determined, which will allow to identify weak points in the management of bunkering processes, to design processes for the restoration of technical objects, to predict the level of performance of contracts and promising directions for updating the technical and technological base.